Production Process of Sugarcane Bagasse for the Generation of Bio-Products and Biofuel: An Overview - , Archana Singh; Kanchan; Sadhvi, Meenakshi Saxena, NK Sharma (Archives of Current Research International, 2024)
One of the main agricultural products grown in tropical nations is sugarcane. An estimated 1.6 billion tons of sugarcane are produced worldwide each year, and from that, 279 million metric tons (MMT) of biomass residues—bagasse and leaves—are produced. Sugarcane residues have been investigated for both non-biotechnological and biotechnological uses, in particular sugarcane bagasse (SB) and leaves (SL). The use of SB and SL in lignocellulosic bioconversion has been investigated for the past thirty years. This process presents prospects for the profitable use of leftover substrates in the synthesis of bioethanol and value-added commercial products like xylitol, specialty enzymes, organic acids, single-cell protein, etc. However, the development of bio-based commercial processes using SB and SL as basic substrates still faces significant technological and financial obstacles. The need to find a cost-effective and environmentally safe gasoline substitute stems from the depletion of fossil fuel reserves, frequent increases in gasoline prices, and harm to the environment. Due to the growing needs for fuel, food, feed, and other resources, the use of ethanol as an energy source does not appear appropriate in the long run. Ethanol is created from substrates that are derived from food and feed, such as grains, sugars, and molasses. However, the development of bio-based commercial processes using SB and SL as basic substrates still faces significant technological and financial obstacles. In order to better understand their industrial consequences, their application in commercial products, including commercial evaluation, and their potential to improve sustainable bio-based fuel systems, this article will examine SB and SL as less expensive sources of carbohydrates in developing countries.